BENEFITS OF CINNAMON CONSUMPTION IN PATIENTS WITH GOUT ARTHRITIS - Martha Sella Rianti (Ibnu Sina: Jurnal Kedokteran dan Kesehatan - Fakultas Kedokteran Universitas Islam Sumatera Utara, 2020)
Gout arthritis is a condition where an increase in uric acid levels can trigger the formation of crystals that can cause pain in the joints. Management of gouty arthritis can be done by pharmacological and non-pharmacological ways. Recently treating the disease using medicinal plants is increasingly in demand. One of the plants that has the potential as a cure for gouty arthritis is cinnamon (Cinnamomum burmanii). This review was compiled by searching library sources through NCBI, Garuda, Sinta and Google Scholar. The results of an article search found that consumption of cinnamon in patients with gouty arthritis is useful as an anti-inflammatory. This is because the content of cinnamaldehyde in cinnamon can inhibit lipoxygenase. The function of lipoxygenase is that it can convert free arachidonic acid into leukotriene. If the level of leukotrienes in the body falls, the inflammatory process will decrease